Low Accuracy of FIB-4 and NAFLD Fibrosis Scores for Screening for Liver Fibrosis in the Population - Graupera, Isabel; Thiele, Maja; Serra-Burriel, Miquel; Caballeria, Llorenç; Roulot, Dominique; Wong, Grace Lai-Hung; Fabrellas, Núria; Guha, Indra Neil; Arslanow, Anita; Expósito, Carmen; Hernández, Rosario; Aithal, Guruprasad Padur; et al. (Clinical gastroenterology and hepatology, 2022)
Fibrosis-4 (FIB-4) and the nonalcoholic fatty liver disease fibrosis score (NFS) are the 2 most popular noninvasive blood-based serum tests proposed for widespread fibrosis screening. We therefore aimed to describe the accuracy of FIB-4 and NFS to detect elevated liver stiffness as an indicator of hepatic fibrosis in low-prevalence populations. This study included a total of 5129 patients with concomitant measurement of FIB-4, NFS, and liver stiffness measurement (LSM) by Fibroscan (Echosens, France) from 5 independent population-based cohorts from Spain, Hong Kong, Denmark, England, and France; 3979 participants from the general population and 1150 from at-risk cohorts due to alcohol, diabetes, or obesity. We correlated LSM with FIB-4 and NFS, and calculated pre- and post-test predictive values of FIB-4 and NFS to detect elevated LSM at 8 kPa and 12 kPa cutoffs. The mean age was 53 ± 12 years, the mean body mass index was 27 ± 5 kg/m2, and 2439 (57%) were women. One in 10 patients (552; 11%) had liver stiffness ≥8 kPa, but 239 of those (43%) had a normal FIB-4, and 171 (31%) had normal NFS. The proportion of false-negatives was higher in at-risk patients than the general population. FIB-4 was false-negative in 11% of diabetic subjects, compared with 2.5% false-negatives with NFS. Waist circumference outperformed FIB-4 and NFS for detecting LSM ≥8 kPa in the general population. Almost one-third (28%–29%) of elevated FIB-4/NFS were false-positive in both the general population and at-risk cohorts. FIB-4 and NFS are suboptimal for screening purposes due to a high risk of overdiagnosis and a non-negligible percentage of false-negatives, especially in patients with risk factors for chronic liver disease. Waist circumference emerged as a potential first step to identify patients at risk for liver fibrosis in the general population.